Physical activity levels and eating habits of students in different educational levels - Hoca, Mustafa; Özduran, Gülşen (Progress in Nutrition, 2021)
Aim: People stay being healthy, they must be able to have healthy behaviors to prevent development of chronic non-communicable diseases. Because of being healthy lifestyle, individuals can acquire healthy eating habits and do physical activity regularly. This study was designed to assess physical activity levels and eating habits and its association with the health-promoting lifestyle profile of Audiology students in different educational levels. Materials and Methods: Total 201 male and female students were participated from Department of Audiology, Near East University, Northern Cyprus. In this study, the short form of International Physical Activity Questionnaire was applied for assessing the physical activity levels. Physical activity levels were classified as inactive, minimum active and active. Furthermore, Health-Promoting Lifestyle Profile II scale was used to determine situation of healthy lifestyles. Results: A statistically significant negative and weak correlation was detected between the International Physical Activity Questionnaire score and stress management score. Furthermore, a statistically significant positive and weak correlation was found between the quantity of main meals and total Health-Promoting Lifestyle Profile II score. Conclusion: This study showed that Health-Promoting Lifestyle Profile II subscales’ scores of students influenced by their physical activity levels. Stress is one of the notable factors in healthy behavior changes. Consequently, health-promoting educational programs should be developed.